Enforcement of Law Number 22 of 2009 concerning Road Traffic on Vehicle Speed ​​Limits on Toll Roads: Penegakan UU Nomor 22 Tahun 2009 tentang Lalu Lintas Jalan terhadap Batas Kecepatan Kendaraan Dijalan Tol - Firdausi, Muhammad Farrel Alaysia; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2020)
The research method used in this paper is a sociological juridical method, which means a research on legal materials that serves to see the law in a real sense and examines how the law works in the community. It can also be said that legal research is taken from the factors that exist in a community, legal entity or government. The results of this study are according to existing rules, the actual speed limit of vehicles is on the toll road 60km/hour and a maximum of 100km/hour, but the reality is that in the field there are still many road users who violate these rules. reports from members who are at their respective reconnaissance places using a tool called a speed gun to determine the speed of passing vehicles, the ticket itself is carried out at the toll exit. As for the obstacles themselves for the PJR Jatim 2 unit so far there have been none because everything went smoothly, while the obstacle was during the rainy season, namely the rain that made it difficult for members to measure the speed of passing vehicles because in the field clearly needed views and good weather to measure vehicle speed.